Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Pada Produk Sepatu Adidas - Mariam, Siti Risda; Lahat, Mohammad amas; Utama, Dani chandra (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the influence of product quality and brand image on purchasing decisions for the latest Adidas shoe products. A deep understanding of factors influencing consumer preferences is crucial for business sustainability in a competitive market context. The research method employed was a quantitative approach, disseminating questionnaires to 100 respondents who are consumers of Adidas shoes. The collected data were analyzed using multiple linear regression. The t-test results indicate that product quality has a positive and significant influence on purchasing decisions (t=4.041, p=0.000), and similarly, brand image also shows a positive and considerable influence (t=4.148, p=0.000). Furthermore, the F-test results demonstrate that product quality and brand image significantly influence purchasing decisions (F=44.787, p=0.000). These findings indicate that intrinsic product aspects and brand perception collectively play a central role in driving consumer purchasing decisions. Thus, this research affirms that improving product quality and strengthening brand image are effective strategies for Adidas to win the competition and maintain consumer loyalty